2017
DOI: 10.1128/aac.02127-16
|View full text |Cite
|
Sign up to set email alerts
|

Perifosine Mechanisms of Action in Leishmania Species

Abstract: Here the mechanism by which perifosine induced cell death in Leishmania donovani and Leishmania amazonensis is described. The drug reduced Leishmania mitochondrial membrane potential and decreased cellular ATP levels while increasing phosphatidylserine externalization. Perifosine did not increase membrane permeabilization. We also found that the drug inhibited the phosphorylation of Akt in the parasites. These results highlight the potential use of perifosine as an alternative to miltefosine against Leishmania. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…In our study, the observed alteration levels of the mitochondrial potential in PHs-treated parasites did not reach significant low values when compared to the control thus indicating that the machinery of the mitochondria was still able to continue with its functions, which is in accordance with the maintained ATP levels mentioned above. Moreover, similar observations regarding the alteration levels of the mitochondrial potential, have been detected in previous studies even using the reference drug, miltefosine [36].…”
Section: Discussionsupporting
confidence: 85%
“…In our study, the observed alteration levels of the mitochondrial potential in PHs-treated parasites did not reach significant low values when compared to the control thus indicating that the machinery of the mitochondria was still able to continue with its functions, which is in accordance with the maintained ATP levels mentioned above. Moreover, similar observations regarding the alteration levels of the mitochondrial potential, have been detected in previous studies even using the reference drug, miltefosine [36].…”
Section: Discussionsupporting
confidence: 85%
“…In fact, the presence of high levels of ROS can cause increased levels of lipid peroxidation and reduction in membrane fluidity, leading to the loss of cell viability [ 55 , 58 ]. Mitochondria have been considered a target when distinct antileishmanial agents were tested [ 7 , 28 , 35 , 57 , 63 ]; however, contrarily to what was observed in mammalian cells, where this organelle is abundant in their content, Leishmania spp. and other trypanosomatids present only one mitochondrion, which exhibits functional and morphological differences, such as the presence of its own genetic material, peculiarities in the functionality of the electron transport chain, and existence of non-canonical antioxidant machinery [ 2 , 24 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Experiments were carried out with L. amazonensis (MHOM/BR/77/LTB0016) and L. donovani (MHOM/IN/90/GE1F8R) strains. The activity of the compounds was tested in vitro against the promastigote stage of T. cruzi , L. amazonensis , and L. donovani according to described methodology . The positive control for Leishmania spp.…”
Section: Methodsmentioning
confidence: 99%
“…The activity of the compounds was tested in vitro against the promastigote stage of T. cruzi, L. amazonensis, and L. donovani according to described methodology. [18,19] The positive control for Leishmania spp. was miltefosine that has an IC 50 of 6.48 and 3.32 μM for L. amazonensis and L. donovani, respectively.…”
Section: -Di-o-methoxyphenylacetyl-25hydroxy-dammaran-20-ene (2a)mentioning
confidence: 99%